2010
DOI: 10.1111/j.1744-6198.2009.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunizing Children Who Fear and Resist Needles: Is It a Problem for Nurses?

Abstract: The following four overarching themes were identified and are used to explain and describe significant features of the immunization experience that were stressful and problematic for nurses: (a) nurses experience stress when immunizing children who fear and resist needle injection; (b) the strength of child resistance and some adult behavior creates an ethical dilemma for nurses; (c) some adult responses make immunizing difficult and unsafe; and (d) resources to help nurses cope with these situations are incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This in turn can lead to physical harm for the nursing staff (Lambrenos & McArthur, 2003) and children respectively, and Llyod, Urquhart, Heard, and Kroese (2008) find that nurses experience negative emotions during this action. In a study by Ives and Melrose (2010), the nurses described a feeling of powerlessness when the children had to endure those trying NRMP. Similarly, the nurses in our study reflected upon the negative consequences of a difficult procedure for the children but also for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn can lead to physical harm for the nursing staff (Lambrenos & McArthur, 2003) and children respectively, and Llyod, Urquhart, Heard, and Kroese (2008) find that nurses experience negative emotions during this action. In a study by Ives and Melrose (2010), the nurses described a feeling of powerlessness when the children had to endure those trying NRMP. Similarly, the nurses in our study reflected upon the negative consequences of a difficult procedure for the children but also for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Kangasniemi et al (2014) found that nurses considered restraint important because it eased their work and fulfilled the aim of good nursing care because restraint was held to be best for the patient. In other studies, nurses who saw restraint as unacceptable could find it difficult to choose between causing harm and promoting health (Ives & Melrose, 2010; Lloyd, Urquhart, Heard, & Kroese, 2008; McGrath & Huff, 2003). Delaney (2001) performed an ethical analysis of nurses’ perspectives on the harm of restraint versus the benefit in psychiatric settings and concluded that holding a child was perceived as “reasonable harm” compared with the benefit of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main rule in Norwegian health law, as in international human rights guidelines, is that any use of coercion requires an explicit legal authority, a formal decision, and appeal procedures. The lack of clear guiding principles for when and how to use restraint can create professional and ethical challenges for healthcare providers and may influence their clinical judgments (Ives & Melrose, 2010). Since restraint in this setting is not specifically regulated and generally not accompanied by a formal decision and documentation, the restraint used can be defined as “informal” restraint.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, children are still held in order for clinical procedures to be completed. Within healthcare settings, being held or restrained can be a highly traumatic and distressing experience for children, parents (McGrath et al 2002) and health professionals (Chuang and Huang 2007;Bigwood and Crowe 2008;Smith and Bowman 2009;Ives and Melrose 2010). Being restrained can result in children experiencing short-term distress and long-term negative psychosocial development (Brenner 2013).…”
Section: Introductionmentioning
confidence: 99%